ZC3H7B-BCOR high-grade endometrial stromal sarcoma with osseous metaplasia: Unique feature in a recently defined entity - Jerry C. Nagaputra; Ronald Chin Hong Goh; Chik Hong Kuick; Kenneth Tou En Chang; Kesavan Sittampalam (Elsevier, 2019)
High-grade endometrial stromal sarcoma harboring ZC3H7B-BCOR fusion is a newly defined entity in gynecologic pathology featuring a set of distinct histopathological and molecular features. It is morphologically characterized by atypical ovoid to spindle cells with a fascicular architecture, usually embedded within a myxoid stroma. Unlike high-grade endometrial stromal sarcoma associated with YWHAE-NUTM2 fusion, the neoplastic cells are consistently immunoreactive to CD10. It may be confused with myxoid leiomyosarcoma and carcinosarcoma, although the expression of myoid and epithelial markers is absent or very limited. Osseous metaplasia has not been previously described in this tumor. The presence of osseous metaplasia may raise the differential diagnosis of ossifying fibromyxoid tumor, which is also associated with ZC3H7B-BCOR fusion. The clinical prognosis is poor with disease progression in all cases described thus far. In this report, we describe a 52-year-old Singaporean woman of Chinese descent with ZC3H7B-BCOR high-grade endometrial stromal sarcoma containing focal osseous metaplasia.